Are Political Representatives More Risk-Loving Than the Electorate? Evidence from German Federal and State Parliaments - Moritz Heß; Christian von Scheve; Jur̈gen Schupp; Aiko Wagner; Gert G. Wagner (Palgrave Communications, 2018)
Political representatives frequently make decisions with far-reaching implications for citizens and societies. Most of these decisions are choices in situations in which the probabilities of gains and losses are hard to estimate. Although decision-making is crucial to politics, existing research has hardly ever addressed the political representation of traits that notably influence decision-making. One such trait is risk propensity; that is, an individual's willingness to take risk. Using a unique dataset consisting of representative samples of the German Federal Parliament, four German State Parliaments, and the general German population, the present study investigates the degree to which political representatives' risk propensity resembles their constituents' appetite for risk. Not only descriptive results but even after using matching techniques and controlling for several potentially confounding variables, the study shows that political representatives are significantly more risk loving than the average citizen across several domains of risk taking. The implications of this finding are twofold. First, it points at a representation gap suggesting that politicians tend towards riskier choices than their voters, which not only affects politicians themselves but the entire polity. Second, it suggests a useful `division of labor' according to which risk-loving politicians are prepared to take risks in exceptional situations, which their constituents would eschew.
Keywords: 330